Niemann-Pick Disease: An Underdiagnosed Lysosomal Storage Disorder - Inusha Panigrahi; Manoj Dhanorkar; Renu Suthar; Chanchal Kumar; Mullai Baalaaji; Babu Ram Thapa; Jasvinder Kalra (Case Reports in Genetics)
Lysosomal storage disorders (LSDs) collectively constitute a significant public health burden in developing countries. Commoner LSDs include Gaucher, Fabry, and Niemann-Pick disease (NPD), but many cases remain undiagnosed. With the high incidence of consanguineous marriages, South East Asian countries are expected to have high prevalence of these LSDs. Here we report 4 cases of NPD type A/B in 3 families presenting with hepatosplenomegaly and cytopenias including one family with two sibs having hypertension and mitral valve prolapse. The diagnosis of NPD was proven by mutation analysis with identification of novel mutations, including a novel 4 bp insertion mutation (C>CCTGG) in exon 2 of the SMPD1 gene. We also had two cases of NPD type C, confirmed on mutation analysis.